2017
DOI: 10.1371/journal.pone.0188685
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Prunus mira (Koehne) from the Tibet plateau in China and recommended conservation strategies

Abstract: Prunus mira Koehne, an important economic fruit crop with high breeding and medicinal values, and an ancestral species of many cultivated peach species, has recently been declared an endangered species. However, basic information about genetic diversity, population structure, and morphological variation is still limited for this species. In this study, we sampled 420 P. mira individuals from 21 wild populations in the Tibet plateau to conduct a comprehensive analysis of genetic and morphological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
3
15
1
Order By: Relevance
“…Similar studies performed with other species revealed quite similar results. Bao et al (2017) found that in Prunus mira (Koehne), geographic distance is not a crucial factor for genetic composition in small areas, and an altitude gradient can have more significant effects on population structure than geographical distance. In addition, Tang et al (2014), observed in Lilium pumilum DC that altitude, mean annual temperature, and mean annual rainfall contribute 9.5, 11.5, and 14.0% of the total variance among the populations, respectively.…”
Section: Implications Of Altitude For Conservation and Breeding Of Fementioning
confidence: 98%
“…Similar studies performed with other species revealed quite similar results. Bao et al (2017) found that in Prunus mira (Koehne), geographic distance is not a crucial factor for genetic composition in small areas, and an altitude gradient can have more significant effects on population structure than geographical distance. In addition, Tang et al (2014), observed in Lilium pumilum DC that altitude, mean annual temperature, and mean annual rainfall contribute 9.5, 11.5, and 14.0% of the total variance among the populations, respectively.…”
Section: Implications Of Altitude For Conservation and Breeding Of Fementioning
confidence: 98%
“…For instance, K. latifolia populations at the southernmost range usually have a flowering time one month earlier than populations in Massachusetts according to our investigation. This gap in blooming period, coupled with the large geographic distance, could prevent insect pollination [37]. Therefore, a relatively higher level of among-population differentiation was observed on K. latifolia than other out-crossing species.…”
Section: Genetic Diversity and Differentiation Of K Latifoliamentioning
confidence: 99%
“…Frequent gene flow led to low level of genetic differentiation and small genetic distance between them [38]. By contrast, gene flow between populations inhabiting different geographic regions was reduced because of different phenological phases (e.g., blooming time) caused by different environmental conditions [37]. In addition to limited gene flow, the result of plants' adaptations to different growing conditions might also account for the higher level of genetic differentiation and larger genetic distance between populations that distribute in different geographic regions.…”
Section: Population Structure Of K Latifoliamentioning
confidence: 99%
“…In a previous field survey, Zeng [7] observed that many wild P. mira trees in the Tibet region were male sterile. The high proportion of male sterility trait may have contributed to the high genetic variation observed in P. mira [8,9].…”
Section: Introductionmentioning
confidence: 99%